Analysis of Numeration Literacy Learning Content on the Character of Primary School Students 060970 Medan Belawan - Muhammad Dekar; Zulvia Misykah; Rudi Hermansyah Sitorus; Muhammad Ridho (FKIP, Universitas Palangka Raya, 2025)
One of the main components of the independent curriculum is character and numeracy learning. These two components are among the abilities that elementary school students must have. The aim of this research is to look at problems in learning numeracy and character literacy which are requirements for making learning products. This research is qualitative and uses interviews and observations. The subjects of this research were teachers and students of class IV SDN 060970 Medan Belawan. The results of data analysis show that this research focuses on three main themes: lack of teaching materials to improve numeracy literacy skills, lack of numeracy literacy training, and behavioral problems related to character. Future researchers can use the findings of this research to assess the need to create learning models, learning modules, and teacher guidebooks that aim to improve students' numeracy skills and character.